2007
DOI: 10.1243/09544070jauto51
|View full text |Cite
|
Sign up to set email alerts
|

Testing of an automobile exhaust thermoelectric generator in a light truck

Abstract: Testing was conducted on a prototype automobile exhaust thermoelectric generator (AETEG) installed in a 1999 GMC Sierra pick-up truck. The system consisted of the generator, its power conditioning unit, and the interfaces to the test truck's engine coolant and exhaust systems. The objective of the test was to measure the AETEG's performance and its effect on the truck systems as well as to determine which factors are important for optimizing an AETEG design. Testing was performed in a dynamometer-equipped wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(69 citation statements)
references
References 2 publications
0
58
0
8
Order By: Relevance
“…1e2% can be recovered today e.g. through thermal electric generators (Thacher et al, 2007), fuel economy improvements of up to 5% are projected (Friedrich et al, 2007).…”
Section: Improving Drivetrain Efficiencymentioning
confidence: 99%
“…1e2% can be recovered today e.g. through thermal electric generators (Thacher et al, 2007), fuel economy improvements of up to 5% are projected (Friedrich et al, 2007).…”
Section: Improving Drivetrain Efficiencymentioning
confidence: 99%
“…1,2) A number of studies have addressed the TEG systems as a thermal energy recovery method in automobiles. [3][4][5][6] According to previous research achievements, it can be concluded that a high-efficiency heat exchanger is necessary to increase the amount of heat energy extracted from the exhaust gas. Continuous efforts have been made to maximize their efficiency, with methods mainly concentrating on changing the structure of the heat exchanger and introducing different heat transfer enhancement measures.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous efforts have been made to maximize their efficiency, with methods mainly concentrating on changing the structure of the heat exchanger and introducing different heat transfer enhancement measures. Although a lot of types of heat exchanger for exhaust gas have been proposed, [7][8][9][10][11][12][13][14][15][16] little has been reported on waste heat recovery, such as radiant heat from steel products.…”
Section: Introductionmentioning
confidence: 99%
“…5 Further, many research teams have successfully embedded thermoelectric generators in vehicles, which recycle the waste heat generated by the heat exchanger. 6,7 However, the low conversion efficiency of current thermoelectric power generation systems, coupled with the high cost of modules, has limited their applications. If these shortcomings are addressed, TE modules could see greater use and lead to a significant reduction in waste energy in the form of heat.…”
Section: Introductionmentioning
confidence: 99%